LARANGAN PERKAWINAN DI ANTARA DUA KHOTBAH: TINJAUAN HUKUM ISLAM ATAS PRAKTIK PERKAWINAN DI DESA SIBIRUANG KABUPATEN KAMPAR RIAU - Mustafid, Mustafid (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2016)
In the Islamic law there is a marriage prohibition related to time, which is a prohibition on getting married when a person performs ihram, both the ihram of hajj and ihram of umrah and in the iddah period. The people of Sibiruang Village, Koto Kampar Hulu District, Kampar Regency, Riau Province, besides adhering to Islamic law, are still firmly adhered to the customs that have been passed hereditary to the prohibition of marriage between two praying sermons of Eid al-Fitr and Eid al-Adha or from the 1st Shawwal after the Eid al-Fitr to 10 Zulhijjah before the Eid al-Adha. Sibiruang people believe if someone violates, he will get a negative impact on the life of his family someday. This articlewants to examine the marriage prohibition between two praying sermons of Eid al-Fitr and Eid al-Adha and the traditional custom sanctions for those who break the perspective of Islamic law.[Dalam hukum Islam terdapat larangan perkawinan yang berkaitan dengan waktu, yaitu larangan untuk melakukan perkawinan ketika seseorang melakukan ihram, baik ihram haji maupun ihram umrah, dan pada masa iddah. Masyarakat Desa Sibiruang Kecamatan Koto Kampar Hulu Kabupaten Kampar Propinsi Riau, selain berpegang teguh pada hukum Islam, juga masih perpegang teguh pada adat kebiasaan yang sudah turun-temurun terhadap larangan melakukan perkawinan di antara dua Khotbah Idul Fitri dan Khotbah Idul Adha atau dari mulai tanggal 1 Syawal setelah Khotbah Idul Fitri sampai dengan 10 Zulhijjah sebelum Khotbah Idul Adha. Masyarakat Sibiruang meyakini apabila ada yang melanggar akan mendapatkan dampak negatif terhadap kehidupan keluarganya kelak. Tulisan ini ingin mengkaji larangan menikah di antara dua Khotbah Idul Fitri dan Khotbah Idul Adha dan sanksi adat bagi yang melanggarnya perspektif hukum Islam.]